TIPS DAN TRIK SUKSES TES KEMAMPUAN AKADEMIK BAGI SISWA KELAS XII SMK NEGERI 3 SOLOK - Fera Zora; Fajri Basyirun; Ikhwan Ikhwan; Desi Armi Eka Putri; Hendro Masril Saputra (PUAN INDONESIA, 2026)
This community service activity aimed to improve students' understanding and readiness in facing the Academic Competency Test (TKA). The activity was conducted at SMK Negeri 3 Solok involving 154 students of grade XII from Hospitality, Culinary, and Fashion Design departments. The methods used consisted of interactive lectures, question analysis sessions, and simulations. The results showed that students' understanding of TKA characteristics and problem-solving strategies improved. Approximately 90% of participants stated that the simulation helped them understand the types of questions better, while 100% of students considered the explanation of tips and strategies easy to understand. The activity also increased students' confidence and time management skills in answering TKA questions. Therefore, continuous assistance is needed to strengthen students' readiness in facing higher education entrance examinations.